(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Phraseology often used in journalism, literature and law. Its properties are used in the relationship of certain situations, and professional sectors. The terminology in the field of law, consisting of phraseology is corresponded with the court case. Finally, counsel take into consideration the psychological aspect of the prosecutor and by defense counsel. Therefore, a lawyer can fundamentally change the course of events. Educated lawyer always knows how and where to apply the necessary terminology.